Gait stability in k-pop professional dancers - Jang, Y. K.; Hong, S. Y.; Jang, I. (Korean Journal of Sport Biomechanics, 2016)
Objective: The purpose of this study was to provide data on gait characteristics of K-pop professional dancers. Method: Participants were divided into four groups: male dancers (n=10, age: 28.2 ± 3.4 years, height: 175 ± 6 cm, weight: 68.9 ± 5.6 kg), female dancers (n=10, age: 26.7 ± 3.1 years, height: 162 ± 4 cm, weight: 52.1 ± 3.7 kg), non-dancer males (n=10, age: 25.2 ± 2.6 years, height: 171 ± 6 cm, weight: 66.4 ± 5.3 kg), or non-dancer females (n=10, age: 26.2 ± 3.0 years, height: 161 ± 5 cm, weight: 56.4 ± 6.7 kg). Twelve infrared cameras (Qualisys, Oqus 500, Sweden, 150 Hz.) were used to capture three-dimensional motion data. Gait motion data of professional dancers and ordinary persons were obtained. Results: K-pop dancers' dynamic stability during the female toe off event and the male heel contact event was better compared with that of ordinary persons in the front-rear direction. In addition, the results showed a significant difference in the margin of stability (MoS). However, the medial-lateral direction of both female and male dancers during heel contact and the toe off event was more stable compared with ordinary person, who exhibited an increased MoS than did the dancers. Conclusion: This study aimed to investigate the gait characteristics of K-pop professional dancers in comparison with ordinary persons using gait parameters and MoS. The stability of K-pop professional dancers' dynamic gait in the front-rear direction was better than that in the medial-lateral direction. Therefore, further studies in which the dance movements of K-pop dancers are sub-divided and analyzed will be necessary to reduce related injury.